Subacute measles encephalitis in a case of late presenting congenital HIV with epilepsia partialis continua as the first manifestation: A case report - Chakraborty, Arka; Ray, Adrija; Mukherjee, Debaleena; Gupta, Subhadeep; Pandit, Alak; Dubey, Souvik (Journal of family medicine and primary care, 2021)
We report a case of a 14-year-old non-immunised girl with a prior history of measles infection presenting with afebrile seizures progressing to epilepsia partialis continua (EPC), quadriparesis and headache. Further evaluation revealed Human immunodeficiency virus (HIV) seropositivity with elevated anti-measles antibody titres in Cerebrospinal fluid (CSF). Electroencephalography showed focal epileptiform activity and Magnetic resonance imaging (MRI) of the brain revealed bilateral, asymmetrical long repetition time MRI (TR) hyperintensities involving juxtacortical white matter in both parietal lobes, left temporal and also in the left basal ganglia without any contrast enhancement or Diffusion weighted imaging (DWI) restriction. We describe the intriguing association of EPC with subacute measles encephalitis/measles inclusion body encephalitis (SME/MIBE) in the backdrop of immunocompromised state (HIV seropositivity), thought to have been acquired by vertical transmission. Also, prolonged asymptomatic HIV infection, first unmasked by measles infection, followed by rapidly deteriorating neurological illness makes this index case worthy to be reported.